Dravet syndrome: A systematic literature review of the illness burden - Adam Strzelczyk; Lieven Lagae; Jo M Wilmshurst; Andreas Brunklaus; Pasquale Striano; Felix Rosenow; Susanne Schubert‐Bast (Epilepsia Open, 2023)
Abstract We performed a systematic literature review and narrative synthesis according to a pre‐registered protocol (Prospero: CRD42022376561) to identify the evidence associated with the burden of illness in Dravet syndrome (DS), a developmental and epileptic encephalopathy characterized by drug‐resistant epilepsy with neurocognitive and neurobehavioral impairment. We searched MEDLINE, Embase, and APA PsychInfo, Cochrane's database of systematic reviews, and Epistemonikos from inception to June 2022. Non‐interventional studies reporting on epidemiology (incidence, prevalence, and mortality), patient and caregiver health‐related quality of life (HRQoL), direct and indirect costs and healthcare resource utilization were eligible. Two reviewers independently carried out the screening. Pre‐specified data were extracted and a narrative synthesis was conducted. Overall, 49 studies met the inclusion criteria. The incidence varied from 1:15 400–1:40 900, and the prevalence varied from 1.5 per 100 000 to 6.5 per 100 000. Mortality was reported in 3.7%–20.8% of DS patients, most commonly due to sudden unexpected death in epilepsy and status epilepticus. Patient HRQoL, assessed by caregivers, was lower than in non‐DS epilepsy patients; mean scores (0 [worst] to 100/1 [best]) were 62.1 for the Kiddy KINDL/Kid‐KINDL, 46.5–54.7 for the PedsQL and 0.42 for the EQ‐5D‐5L. Caregivers, especially mothers, were severely affected, with impacts on their time, energy, sleep, career, and finances, while siblings were also affected. Symptoms of depression were reported in 47%–70% of caregivers. Mean total direct costs were high across all studies, ranging from $11 048 to $77 914 per patient per year (PPPY), with inpatient admissions being a key cost driver across most studies. Mean costs related to lost productivity were only reported in three publications, ranging from approximately $19 000 to $20 000 PPPY ($17 596 for mothers vs $1564 for fathers). High seizure burden was associated with higher resource utilization, costs and poorer HRQoL. The burden of DS on patients, caregivers, the healthcare system, and society is profound, reflecting the severe nature of the syndrome. Future studies will be able to assess the impact that newly approved therapies have on reducing the burden of DS.